Optical Modification of Monolayer MoS2: Deterministic Modification of CVD Grown Monolayer MoS2 with Optical Pulses (Adv. Mater. Interfaces 10/2021). Issue 10 (24th May 2021) - Turunen, Mikko T.; Hulkko, Eero; Mentel, Kamila K.; Bai, Xueyin; Akkanen, Suvi‐Tuuli; Amini, Mohammad; Li, Shisheng; Lipsanen, Harri; Pettersson, Mika; Sun, Zhipei
Abstract : In article number 2002119, Mika Pettersson, Zhipei Sun, and co‐workers demonstrate an optical modification process that simultaneously creates topographical structures and alters the optical properties of MoS2 monolayer. This local and controllable optical modification method shows great promise for applications in electronics, photonics, and mechanics.